Effects of multiple-dose ponesimod, a selective S1P1 receptor modulator, on lymphocyte subsets in healthy humans - Jurcevic, Stipo; Pierre-Eric Juif; Hamid, Colleen; Greenlaw, Roseanna; D'Ambrosio, Daniele; Dingemanse, Jasper (Drug design, development and therapy, 2017)
This study investigated the effects of ponesimod, a selective S1P1 receptor modulator, on T lymphocyte subsets in 16 healthy subjects. Lymphocyte subset proportions and absolute numbers were determined at baseline and on Day 10, after once-daily administration of ponesimod (10 mg, 20 mg, and 40 mg each consecutively for 3 days) or placebo (ratio 3:1). The overall change from baseline in lymphocyte count was -1,292±340×106 cells/L and 275±486×106 cells/L in ponesimod- and placebo-treated subjects, respectively. This included a decrease in both T and B lymphocytes following ponesimod treatment. A decrease in naïve CD4+ T cells (CD45RA+CCR7+) from baseline was observed only after ponesimod treatment (-113±98×106 cells/L, placebo: 0±18×106 cells/L). The number of T-cytotoxic (CD3+CD8+) and T-helper (CD3+CD4+) cells was significantly altered following ponesimod treatment compared with placebo. Furthermore, ponesimod treatment resulted in marked decreases in CD4+ T-central memory (CD45RA-CCR7+) cells (-437±164×106 cells/L) and CD4+ T-effector memory (CD45RA-CCR7-) cells (-131±57×106 cells/L). In addition, ponesimod treatment led to a decrease of -228±90×106 cells/L of gut-homing T cells (CLA-integrin β7+). In contrast, when compared with placebo, CD8+ T-effector memory and natural killer (NK) cells were not significantly reduced following multiple-dose administration of ponesimod. In summary, ponesimod treatment led to a marked reduction in overall T and B cells. Further investigations revealed that the number of CD4+ cells was dramatically reduced, whereas CD8+ and NK cells were less affected, allowing the body to preserve critical viral-clearing functions.